Neglected Questions on the “Forgotten War”: South Korea and the United States on the Eve of the Korean War - Mark Caprio (Japan Focus)
The breakup of the Soviet Union in the early 1990s prodded open the archival doors of once closed regimes releasing interesting information on Soviet-North Korean-Chinese relations during the Cold War. Documents released from these archives contributed new evidence to enrich our understanding of old questions.2 One such question concerns the origins of the Korean War. Documents from these archives demonstrate an active correspondence between the three communist leaders in Northeast Asia—Josef Stalin, Mao Zedong, and Kim Il Sung—regarding the planning and orchestration of this war fought primarily among the two Korean states, the United States, and China.3 This new evidence has encouraged scholars to reformulate fundamental views of this war, particularly its place in Cold War history.The timing of the documents’ release—just as the Soviet-as-enemy image faded, and the post-Cold War rogue state-as-enemy image emerged—is intriguing. This new evidence’s apparent support of North Korean culpability in the war’s origins proved useful to those who accused North Korea of once again breaching regional peace by launching nuclear programs and other provocative activities. They strengthened calls for close vigilance lest the communist state launch a second surprise, unprovoked attack against its southern neighbor. The contribution made by these documents, however, is limited to enhanced understanding of relations between members of the northern triangle (the Soviet Union, China, and North Korea); they contribute little to understanding of the southern triangle (the United States, Japan, and South Korea). This critical limitation does not enter into the analyses of many scholars who have used these documents to update understanding of this war’s origins. The purpose of this paper is to address questions that require attention before we can fully understand the causes of the Korean War. These questions demand information on the interactions by members of the southern triangle prior to the outbreak of conventional war.It is well known that South Korean President Syngman Rhee equaled his North Korean counterpart’s ambitions to use military force to reunite his homeland, and that the United States was determined to prevent his doing so on his own. Were these ambitions aimed at preserving the peace, or preserving control over the war that many perceived as inevitable? If the former, why didn’t the United States (along with the Soviet Union) exert greater efforts to curtail the increasing outbreaks of armed violence that took place between the two Korean states? If the latter, did intelligence gathered by agents in North Korea allow the United States a window to view Kim Il Sung’s intentions? If so, how did it use this information to form a counter strategy? And, did such strategy enter into discussions between Syngman Rhee and high-level U.S. officials?